Open Switch Faults Detection and Localization Algorithm for Three Phases Shunt Active Power Filter based on Two Level Voltage Source Inverter - Benslimane, T. (Elektronika ir Elektrotechnika, 2007)
An open switch faults detection and localization algorithm for shunt three phase active filter topology is proposed. It mainly details converter configuration and examines a simple and reliable optimised fault diagnosis method. The converter topology is based on classical three-leg active power filter topology. A new fault diagnosis method is proposed, based on classical currents measurements. It includes combinatory logic to analyse and validate error signals. A Hysteresis Control is applied before and after fault detection, which avoids any controller reconfiguration. Simulation results obtained with Matlab/Simulink/Plecs tools prove the effectiveness of this method. Ill. 6, bibl. 8 (in English; summaries in English, Russian and Lithuanian).